Influence Of Brand Attributes to Brand Awareness in Nala Husada Dental Hospital - Ghita Hadi Hollanda; Aulia Dwi Maharani (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2018)
Background: The company is able to be the basis of the formation of customer loyalty and fanaticism of the product or service through a strong brand. Having a strong brand is a vital aspect for any company, because the advantage gained diverse. Based on the data in 2014 and 2015, it showed the decreased number of patients at the Nala Husada Dental Hospital from 2014 to 2015 amounted to 949 people (8%),as well as the number of patients in the Polyclinic of Dental Specialists, were 14,6% (348 patients) from ideal capacity (2384 patients). Purpose: The aim of this study is to find out the influence of brand attributes to brand awareness in Nala Husada Dental Hospital. Methods: This study was an observational study that used 200 respondences from the patients population of Nala Husada Dental Hospital. The study was conducted at Nala Husada Dental Hospital from March-April 2018. Results: The results showed that the characteristics of patients who seek treatment at the Nala Husada Dental Hospital were majority adults in productive age (25-35 years old), at middle to lower-end of socio-economic class, and had the education level of SLTA grade. Most of respondents had bad perception for the brand attributes of Nala Husada Dental Hospital.Most of them had low brand awarenesstowards the Nala Husada Dental Hospital. There was a tendency if the brand attributes were good, the brand awareness was getting better.